2020
DOI: 10.1002/ijc.33337
|View full text |Cite
|
Sign up to set email alerts
|

Do myeloproliferative neoplasms and multiple myeloma share the same genetic susceptibility loci?

Abstract: Myeloproliferative neoplasms (MPNs) are a group of diseases that cause myeloid hematopoietic cells to overproliferate. Epidemiological and familial studies suggest that genetic factors contribute to the risk of developing MPN, but the genetic susceptibility of MPN is still not well known. Indeed, only few loci are known to have a clear role in the predisposition to this disease. Some studies reported a diagnosis of MPNs and multiple myeloma (MM) in the same patients, but the biological causes are still unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…This phenomenon suggests that CNL may be more inclined to coexist with MGUS or MM instead of coexisting by chance. The common genetic susceptibility loci in MPN and MM, and chronic inflammatory bone marrow microenvironment in MPN that in favor of the proliferation of monoclonal B cells, may be the pathogenesis of concurrence of these two different diseases 15–17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon suggests that CNL may be more inclined to coexist with MGUS or MM instead of coexisting by chance. The common genetic susceptibility loci in MPN and MM, and chronic inflammatory bone marrow microenvironment in MPN that in favor of the proliferation of monoclonal B cells, may be the pathogenesis of concurrence of these two different diseases 15–17 …”
Section: Discussionmentioning
confidence: 99%
“…The common genetic susceptibility loci in MPN and MM, and chronic inflammatory bone marrow microenvironment in MPN that in favor of the proliferation of monoclonal B cells, may be the pathogenesis of concurrence of these two different diseases. [15][16][17] Among the 12 cases we summarized, 11 cases detected CSF3R mutation and 7 cases were positive. We found that CSF3R was the most common mutation among the 12 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, however, that germline variants induce a chronic, low-level of ERBB signaling and subsequent activation of the JAK/STAT, PI3K/AKT, or MEK/ERK pathways, with convergence on common downstream targets. Alternatively, ERBB2 may exert its predisposition to MPN acquisition by pathways that are not intrinsic or specific to hematopoietic cell signaling or development, such as genomic instability, inflammation, telomere biology, or other pathways implicated in cancer susceptibility [17,[45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…12,[21][22][23][24][25] This feature is particularly evident in MM since we observed, using GWAS Catalog, that 17 of the 24 associated polymorphisms ($71%) are pleiotropic or in high linkage disequilibrium (LD) (r 2 > 0.8) with SNPs associated with other traits (https://www. ebi.ac.uk/gwas/), including telomere length, 26 BMI 27 and risk of various cancers, such as myeloproliferative neoplasms 28 and pancreatic cancer. 25 Therefore, the aim of this study was to test the impact of all the SNPs associated at genome-wide significant level with any human trait on risk of MM.…”
Section: Introductionmentioning
confidence: 99%